Ladybird read with me: lets play (key words reading scheme) - Murray, William; Jill Corby (Ladybird Books London, 2011)
A fun reading scheme that uses the ;look and say; approach to learning to read. Essential key words are introduced and regularly repeated to assist with pronunciation and meaning. Level two is for the developing reader.